A theatre of immediacy - Francis, A M (My University, 2014)
imagine. visualise. respond. A Community Theatre provides a social intervention. It energises, transforms and effects change within the social fabric of a community by creating a dialogue for conflict resolution. It presents an opportunity to bridge divisions of race, nationality, gender, class, culture and other barriers through the use of dramatic art therapy by creating a platform for engagement, reflection and understanding. “It was simply the contemporary manifestation of a recurring cultural ideal of an art relegated not to cultural palaces but relevant to daily life, an art whose home is in the streets, in schools, church basements, city parks, and other institutions dear to community life” Ruby Lerner (Cohen-Cruz, 2005, p. 35) Globalisation has resulted in an influx of people to urban areas and created a need for connection and community. The design proposal facilitates dialogue and the search for commonality and connection. This union of divergent voices will reflect collective histories and needs, engendering a community that is empowered to speak, act and be heard. The power of this theatre typology lies with its ability to assist communities in creating both internal and external dialogue about relevant topics affecting them. Current society demands more from its theatre than mere repetitions of foreign and removed realities. It ought to have an immediate and existential impact. (Brook, 1972) The scene is now set for a theatre that helps its community resolve their struggles in a current and contemporary way. One that is not invasive but through its process cathartic, restorative, educational and developmental. (Francis, 2013) This building is an exploration of theatre’s ability to carry its community through adversity via the potency of imagination. It proposes theatre as a mediator and connecting element between community and park. To this end the design of the building is an extension of the park insofar as the undulating roofs of the auditorium reflect the contours of the site and the strategic placement of the performance complex liberates previously underutilised space. Though the detailed analysis of both the urban scale context and the immediate context of the site, I have identified missing elements that are not successfully catered for within the community zone of Yeoville. The programme of a community theatre combines the regular programme associated to a theatre with the specific needs of the community it serves. The design proposal includes two formal performance spaces consisting of a 350 seat thrust stage auditorium and a black box theatre. It provides a divisible outdoor performance space as well as spill-out space for impromptu performances. The functions that separate a community theatre from its traditional counterpart comprise a day-care facility, exhibition space and an arts, crafts and production studio. The use of contextual materials ensures that the theatre complex remains humble within its setting thus redirecting ones focus to the park. This results in a simple structure unfettered by the ostentation of certain traditional theatres. A theatre for now, for then and the future, is only possible if it does indeed give back to its community, helping them grow and learn from its stage.